1985
DOI: 10.1002/anie.198504161
|View full text |Cite
|
Sign up to set email alerts
|

9‐Fluorenylidene‐2,2,6,6‐tetramethylpiperidinoborane: an Allene Isoester with Two‐Coordinated Boron and BC Double Bond

Abstract: The formation of 5a,b is clearly energetically favored over that of the corresponding mononuclear complex containing a P,Ni three-membered ring. Experimental 5a : Freshly distilled Ni(CO), (3.24 g, 19.0 mmol) was added dropwise to a stirred solution of 4 [3] (4.2 g, 18.9 mmol) in n-pentane (50 mL) at 10°C under inert gas. As soon as evolution of CO had ceased, the mixture was warmed to room temperature within 30 minutes and stirred for a further 17-20 h until a total of 38.1 mmol CO had been liberated. The lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(25 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…X-ray crystal-structure analysis of 7 confirmed the presence of adjacent P=Ca nd B=Cu nits in a trans orientation (Figure 3). TheP =Ca nd B=Cb ond distances of 7 are considerably shorter than those in 6 (7:P =C 1.7445 (19), B = C1 .493(3) ; 8:P = C1 .704(3) ,B = C1 .433-(5) ), though the central C1 À C2 bond distance is experimentally indistinguishable from that of 6,a t1 .415(5) .A s expected for amino-substituted methylene boranes, [22] aB ÀN p-bond enforces alinear geometry at the boron center (C=B= Nangle:178.8(4)8 8;B =Nbond distance:1.338(5) ). TheUV/ Viss pectrum of 7 differed substantially from that of 6,w ith as ubstantially blue-shifted longest-wavelength absorption at 365 nm (e = 13 800 Lmol À1 cm).…”
Section: Angewandte Chemiementioning
confidence: 84%
“…X-ray crystal-structure analysis of 7 confirmed the presence of adjacent P=Ca nd B=Cu nits in a trans orientation (Figure 3). TheP =Ca nd B=Cb ond distances of 7 are considerably shorter than those in 6 (7:P =C 1.7445 (19), B = C1 .493(3) ; 8:P = C1 .704(3) ,B = C1 .433-(5) ), though the central C1 À C2 bond distance is experimentally indistinguishable from that of 6,a t1 .415(5) .A s expected for amino-substituted methylene boranes, [22] aB ÀN p-bond enforces alinear geometry at the boron center (C=B= Nangle:178.8(4)8 8;B =Nbond distance:1.338(5) ). TheUV/ Viss pectrum of 7 differed substantially from that of 6,w ith as ubstantially blue-shifted longest-wavelength absorption at 365 nm (e = 13 800 Lmol À1 cm).…”
Section: Angewandte Chemiementioning
confidence: 84%
“…The B-N distance [1.382(5) ] is longer than in 3 [1.300(3) ], in agreement with an increase in electron density at the boron center, but shorter than in 4 [1.460 (3) ]. From these data, and by analogy to aminoboraalkenes, [5] it can be concluded that 5 features an allenic structure as depicted by 5 a.…”
mentioning
confidence: 79%
“…[4] Although the latter are often considered to be the group 13 element analogues of carbenes, they are not isoelectronic with carbenes since they possess one lone pair of electrons but two vacant orbitals. To fulfil the isoelectronic criteria, a Lewis base, such as a singlet carbene, should be appended to borylenes (C), as shown by D. As a matter of fact, such compounds can also be described as alkylideneboranes (D'), but all known derivatives have a formal triplet carbene fragment [5] and therefore feature a conventional double bond. Recently, in efforts to favor carbene-to-boron s donation and boron-to-carbene p backdonation, several groups have attempted to prepare compounds of type D with a stable singlet carbene unit through the reduction of carbene-borane adducts E, [6] G, [7] and I.…”
mentioning
confidence: 99%
“…In terms of B=E double bonds with elements of Group 14, compounds exhibiting a double bond between boron and carbon were reported more than thirty years ago by Berndt, Nöth and Paetzold et al. (Scheme , A – C ) …”
Section: Methodsmentioning
confidence: 99%